Das tastende Ohr: Musikalische Intelligenz und Mündiges Üben - Fuhrmann, Gregor (Georg Olms Verlag, 2014)
To enrich conventional practice with voice or instrument, Das tastende Ohr presents a multi-layered method for inner hearing and mental practice of musical scores. In addition, drawing on the latest scientific findings, it attempts to provide a comprehensive definition of musical intelligence. The combination of theoretical reflection and practical instruction aims to convey a differentiated idea of how, with the help of mature practice, an artistic skill spanning thought, feeling and action can be acquired, maintained and refined.